Trade Policies Support for Palm Oil Downstreaming in Indonesia - Saleh Husin; Chandra Wijaya; Hanief Saha Ghafur; T.M. Zakir Machmud; Eugenia Mardanugraha (JEJAK: Jurnal Ekonomi dan Kebijakan, 2023)
The optimal trade policies are essential to determine the balance between international trade liberalization and protection in order to advance palm oil. Protection is carried out by limiting the export of CPO, while the liberalization applies to raw supporting materials that are not produced in Indonesia. However, the export limitations need to be implemented carefully to avoid counterproductivity to the palm oil industry. This study recommended necessary trade policies to enhance palm oil downstreaming, as well as assessed existing efforts and current policies. This study estimated that a 5% reduction in upstream product export and a 15% increase in downstream product export could rise Indonesian foreign exchange earnings by approximately 7 million USD annually. Descriptive statistics and value-added calculations were employed in this study. Indonesia should restrict the Crude Palm Oil (CPO) towards the countries that exclusively involved in the palm oil trade, guaranteeing that Indonesian palm oil products reach nations where they are utilized. To protect palm oil downstreaming industries, including food, cosmetics, detergents, chemicals, and animal feed, it is vital to regulate imports. Furthermore, strategic trade policies should be enacted to facilitate the export of these refined products. Strengthened negotiation and diplomatic capabilities are also indispensable.Â